The Design Of Kelom Kasep (Differentiation Strategy In Exploring The Form Design Of Kelom Geulis as Hallmark Of Tasikmalaya) - Asep Sufyan (Balong International Journal of Design, 2018)
Kelom geulis is a typical craft of Tasikmalaya Regency. Distinctive features that make Kelom Geulis interested and unique in the fans’view are the use of mahogany and albasia wood materials carved using embroidery motif techniques with the trademark that shows identity of Tasikmalaya.             Increasingly tighter industrial competition needs a new strategy and development of designs. One of the most strategic strategies is how to find a new market segmentation as well as a pioneer in creating innovations not only as a Follower but also as the first step of the craftsmen to be able to make a solution to his loving things that is well known as design. A good design work is a work of uniqueness and very intelligence in appreciating it to community. Differentiation is a way to create a unique position in the mind of the user, establishing status and market segmentation, and making the product position as a different product from the common products. In designing the design of the clones to be unique and valuable is required a method in the process of differentiation development. The differentiation is examined from aspects of form, feature, performance, durability, reliability, style and design.  Keywords: Differentiation, Design, Kelom.